2008
DOI: 10.1002/jclp.20445
|View full text |Cite
|
Sign up to set email alerts
|

Hypomanic symptoms among first‐time suicide attempters predict future multiple attempt status

Abstract: Past conceptual and empirical works have identified unique differences between multiple suicide attempters, single attempters, and zero attempters, but have overlooked two distinct subgroups of single attempters: true single attempters who will not attempt suicide again, and future multiple attempters who will. Consistent with fluid vulnerability theory, the authors hypothesized that subgroups should have differences in personality traits that can predict if a first-time attempter is likely to attempt suicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…From a clinical perspective, it is possible that insomnia severity serves as an indicator of physiological arousal and psychic agitation. A growing body of research supports the value of agitation as a predictor of future suicide attempts and deaths among psychiatric patients . For example, overarousal and agitation are observed in more than 80% of psychiatric inpatients who die by suicide and suicide attempters admitted to emergency departments .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a clinical perspective, it is possible that insomnia severity serves as an indicator of physiological arousal and psychic agitation. A growing body of research supports the value of agitation as a predictor of future suicide attempts and deaths among psychiatric patients . For example, overarousal and agitation are observed in more than 80% of psychiatric inpatients who die by suicide and suicide attempters admitted to emergency departments .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research supports the value of agitation as a predictor of future suicide attempts and deaths among psychiatric patients. [14,41] For example, overarousal and agitation are observed in more than 80% of psychiatric inpatients who die by suicide and suicide attempters admitted to emergency departments. [42,43] Agitated mood states are more common among men than women, [44][45][46][47] and have a much stronger association with suicide ideation and attempts among men.…”
Section: Depression and Anxietymentioning
confidence: 99%
“…Reinforcing the importance of impulsivity and activation in suicidal behavior, a study of 127 military personnel with suicidal behavior showed that severity of hypomanic symptoms-and not personality disorder-predicted subsequent suicidal behavior [43]. The presence of a substance use disorder increased the risk of suicide attempts; this risk was associated with increased aggression and impulsivity [44].…”
Section: Suicidementioning
confidence: 99%
“…It is known that agitation is linked to suicide, suicidal ideation, and suicide attempts [22][23][24][25][26] , thus making careful diagnosis and treatment very important [24,[26][27][28] . Agitation has lately been studied in BPD [29] , agitated depression [27] , bipolar disorder [30] , and schizophrenia [31] , demonstrating that it is an important therapeutic target [6,18] .…”
mentioning
confidence: 99%
“…Agitation has also been shown to potentially predict the response to novel antidepressant treatment approaches with botulinum toxin [33] . More importantly, it has been found to predict suicidal ideation, suicide attempts, and -using retrospective data -actual suicide [22][23][24][25][26] .…”
mentioning
confidence: 99%